2018
DOI: 10.1093/neuros/nyy012
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Human Nucleus Pulposus-Like Cells Derived From Umbilical Cord to Treat Degenerative Disc Disease

Abstract: The findings of this study demonstrating feasibility and efficacy of NPCs to regenerate NP should spur interest for clinical studies to treat DDD using cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…The transplanted MSC‐derived NPCs survived, migrated, and integrated in the nucleus pulposus (NP) of the intervertebral discs (IVDs). NPC transplantation also improved the water and glycosaminoglycan content of the NP, resulting in an increase in disc height and suggesting regeneration of rabbit NP (Perez‐Cruet et al, ). In another study, human MSCs and their retinal progenitor derivatives were transplanted into rd12 mice retina and survived, dispersed, and integrated in the different layers of the retina.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transplanted MSC‐derived NPCs survived, migrated, and integrated in the nucleus pulposus (NP) of the intervertebral discs (IVDs). NPC transplantation also improved the water and glycosaminoglycan content of the NP, resulting in an increase in disc height and suggesting regeneration of rabbit NP (Perez‐Cruet et al, ). In another study, human MSCs and their retinal progenitor derivatives were transplanted into rd12 mice retina and survived, dispersed, and integrated in the different layers of the retina.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, different stem cell-based regenerative approaches have been applied to cure IVD degeneration, aiming at halting or reversing the degeneration [Perez-Cruet et al, 2018]. Many in vitro studies have shown that mesenchymal stem cells (MSCs) contribute to IVD regeneration by chondrogenic differentiation, which increases the synthesis of aggrecan, collagen I, and collagen II [Aguilera-Castrejon et al, 2017].…”
mentioning
confidence: 99%